Why do we age? The main signs of aging - Ugіs Kletnieks; Audrius Butkevichius; V. V. Hladyshev; S. S. Sоkolovskyi (Zaporozhye State Medical University, 2024)
Aging is a gradual and irreversible pathophysiological process. This is manifested in the decline of tissue and cell functions and a significant variety of pathologies associated with aging, including neurodegenerative diseases, cardiovascular diseases, metabolic disorders, increased risk of diseases of the skeleton and the immune system. Although modern medical advances have made a certain contribution to human health and greatly extended life expectancy, along with the aging of society, various chronic diseases are gradually emerging, which are the most important causes of disability and death of the elderly. Aim. The aim of the work is to analyze modern ideas in the field of causes and manifestations of aging processes for the possibility of developing a strategy to slow down its course. At the molecular and cellular level, aging is a complex biological process involving the gradual deterioration of various cellular and molecular processes in the body over time. The length of a person's life is closely related to the decrease in the possibilities of repair and regeneration of tissues and organs. In response to stress at the molecular, cellular, and systemic levels, genetic, epigenetic, and environmental regulatory factors cause a decrease in the body's physiological capabilities. They use complex molecular mechanisms that together contribute to aging. Molecular mechanisms (such as telomere shortening, accumulation of DNA damage, metabolic changes, and excessive free radical generation) strongly link various factors to the rate of aging. Collectively, these mechanisms inhibit cell proliferation, alter metabolism and gene expression, and induce high levels of free radicals, maintaining a senescent cell phenotype. Although the number of early senescent cells is low, they can limit the regenerative capacity of tissue stem cells and lead to the accumulation of cellular damage, thereby contributing to age-related diseases. Conclusions. Current advances in high-throughput genomics, transcriptomics, proteomics, and metabolomics enable the characterization and quantification of thousands of epigenetic markers, transcripts, proteins, metabolites, and can reveal general changes that occur with age in complex organisms at the molecular level. Thus, the integration of these molecular markers and related molecular mechanisms into a comprehensive assessment of biological age to prevent age-related functional decline and morbidity is becoming an increasingly pressing issue in medical science and should be implemented in practice as soon as possible.